Membangun Pondasi Moral: Penalaran Etis dalam Pendidikan Dasar Melalui Pendekatan Filosofis - Fathan Faqih Ali; Ahmad Ruslan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to analyze ethics-based education methods in elementary schools through a literature review approach, focusing on the role of teachers in shaping students’ moral character. Literature review is a method that collects, analyzes, and synthesizes literature sources to understand related concepts and research results. The results of this study show that teachers play an important role in the formation of students’ moral character, both by modeling values such as honesty, responsibility, and empathy, as well as by teaching ethical discussions and moral dilemmas. This approach helps students understand multiple perspectives and the social consequences of their actions, which develops critical thinking and ethical decision-making skills. The integration of moral values in daily learning as well as the consistency of teacher behavior has proven effective in improving students’ ethical literacy from an early age.